Environmental adaptation in three-spined stickleback - Begum, Mahmuda (2021)
Environmental adaptation of a species driven by different agents of natural selection is a major focus of eco-evolutionary research. In this thesis, I aimed to understand the role of selection in shaping phenotypic and genotypic adaptation of a model fish, the three-spined stickleback (Gasterosteus aculeatus) in relation to different environmental factors. Firstly, I found significant associations between the pH of loch water and patterns of morphological diversity when comparing adaptive divergence on two neighbouring islands, North and South Uist. This suggests the influence of an abiotic agent on natural selection which might be responsible for the adaptive divergence of closely-related lineages. Secondly, I observed substantial variation in phenotypic and genotypic traits among hybrids of ancient marine anadromous and newly-adapted freshwater stickleback populations in a natural hybrid zone in North Uist. Phenotypic traits such as standard length of fish, total plate count and parasite abundance showedmosaic patterns, whereas body shape, all spines and pelvic structure exhibited clinal patterns across the hybrid zone due to adaptive divergence between parental populations. Genetic diversity was also observed using adaptive nuclear and mitochondrial markers of specific candidate loci (Eda, PPARA, WNT7B, NLRC5 and Cytochrome b gene) under selection. There was strong genotypic differentiation between marine and freshwater stickleback populations due to strong direct selection across the geographical range from sea to loch. The phenotype-genotype association of selected adaptive traits indicates the evolutionary consequences of adaptation, by identifying signatures of selection on genomic regions underlying phenotypic traits. Third, I found strong genetic links to parasite resistance underlying adaptation to infection, by examining parasitic abundance in stickleback in both natural and experimental environments. The genotypes of selected adaptive loci (Eda, PPARA, WNT7B and NLRC5) varied in relation to the common ectoparasite (Gyrodactylus sp.) and freshwater endoparasite (Diplostomum pseudospathecum), suggesting a role for parasite-mediated selection in the ecological adaptation of stickleback. Finally, I found both environmental and genetic influences on the relative abundance and diversity of bacterial species in the stickleback skin microbiome. In conclusion, the research presented in this thesis provides a significant insight into divergent phenotypic and genotypic adaptation driven by environmental selection to understand the mechanism of ecological speciation in nature.